PROGRAM PENINGKATAN KETRAMPILAN SUMBER DAYA MANUSIA UNTUK MENDUKUNG MINAT BERWIRAUSAHA - Parwati, Cyrilla Indri; Wibowo, Hary; Sutanta, Edhy (JURNAL GAUNG INFORMATIKA, 2016)
Community Service Program (KKN) is an intrakurikuler activity that combines Tri Dharma Perguruan Tinggi implementation to provide stock to students in the form oflearning experiences and community empowerment. KKN is a vehicle for the application and development of science, technology and arts, carried out outside thecampus, in time, working mechanisms, and certain requirements. KKN program at the Institut Sains & Teknologi AKPRIND Yogyakarta, as well as efforts to improve empathyand awareness of students in the community and apply science, especially science and technology in the midst of society. The process of implementing KKN also get guidance from lecturers. In the guidance of this KKN, lecturers also play a role in the implementation of community service. With the involvement of this lecturer is expectedto implement KKN can run in accordance with the policy of the Institute. Implementation of KKN is done by Gedong Kuning with work program to improve human resource skill to support entrepreneurship interest. Hopefully this program can be implemented well by the community to reduce unemployment and increase income.